Book4paws business plan - Silva, Mariana Carrilho Carvalho da (2017)
Book4Paws is designed to be the one-stop booking site for pet services in Portugal, where pet lovers can look for the best solution to spoil their animals. The humanization of pets by their owners is becoming a trend in our society, which leads to the emergence of new concepts to cover a wide range of needs such as dietary supplements, pet-friendly restaurants and hotels, pet sitting, health insurances, among others. In fact, in 2015 well-being care services accounted for 14% of the industry revenue, which means more than 44 million euros.